Development of Biodegradable Delivery Systems Containing Novel 1,2,4-Trioxolane Based on Bacterial Polyhydroxyalkanoates - Sergei Y. Lipaikin; Ivan A. Yaremenko; Alexander O. Terent’ev; Tatiana G. Volova; Ekaterina I. Shishatskaya (Advances in Polymer Technology)
In this work, delivery systems in the form of microparticles and films containing 1,2,4-trioxolane (ozonide, OZ) based on polyhydroxyalkanoates (PHAs) were developed. Main systems’ characteristics were investigated: the particle yield, average diameter, zeta potential, surface morphology, loading capacity, and drug release profile of microparticles, as well as surface morphology and release profiles of OZ-containing films. PHA-based OZ-loaded microparticles have been found to have satisfactory size, zeta potential, and ozonide loading-release behavior. It was noted that OZ content influenced the surface morphology of obtained systems.